Setrategi Marketing melalui Platform Marketplace untuk Meningkatkan Penjualan Home Industri Keripik Tempe Singkong Desa Prajegan Sukorejo Ponorogo - Wiji Lestari Wahyu Hastuti; Abdah Munfaridatus Sholihah (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This research explores marketing strategies through a marketplace platform to increase sales of the cassava tempeh chips home industry in Dukuh Mening, Prajegan, Sukorejo. By utilizing available marketplace features, such as paid advertising, promotions, and sales data analysis, this research aims to identify the most effective approach in increasing product visibility and sales. The main focus lies on product listing optimization, competitive pricing, and data-driven marketing strategies to reach a wider target market. The research results are expected to provide practical guidance for industry players in implementing effective marketing strategies in the digital era.